Effect of different extenders and cryoprotectants on sperm viability of mud crab, Scylla tranquebarica for short term storage - Zakaria, Siti Nor Fatihah; Hazwani, Nur; Chen, Cheng-Ann (Jurnal Akuakultur Indonesia, 2024)
The aim of the present study was to determine the extenders such as calcium-free saline, Ringer’s solution and phosphate buffer and to determine the effect of different concentrations of cryoprotectants with different duration of exposure for short term storage of mud crab, Scylla tranquebarica sperm cells. A total of 30 mud crabs were used in the present study. In the present study, three treatments with three replicates were tested to determine the suitable extender. Besides, three treatments (dimethyl sulfoxide, glycine and glycerol) were tested to determine the suitable cryoprotectants. Eight treatments (25, 20, 16, 4, 2, -4, -20 and -80 °C) were assessed to determine the optimal cooling rate. The result showed the phosphate buffer solution produced the highest sperm viability (82.36 ± 5.84 %) after 60 min compared the Calcium free saline and Ringer’s solution. The results for sperm viability at -4 °C, -20 C and -80 °C after 24 hours were 95.63 0.13 % (5 % glycine), 91.51 ± 1.91 % (5 % DMSO) and 93.97 ± 0.43 % (5 % glycine). By using the 5 % glycine as the best cryoprotectant, the results for the sperm viability in 6 h, 12 h, 24 h, day 7, day 14 and day 21 at 80 °C were 95.17 ± 0.92 %, 94.11 ± 0.64 %, 93.31 ± 0.51 %, 90.84 ± 2.05 % and 82.82 ± 0.41 %. In a nutshell, the phosphate buffer and 5 % glycine were the best extender and cryoprotectant in the present study.